PEMODELAN MARKOV SWITCHING VECTOR AUTOREGRESSIVE (MSVAR) - Hayuk Permatasari; Budi Warsito; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Economic and financial variables are variables that are fluctuated because of regime switching as a result of political and economical conditions. Linear modeling can not capture the regime switching, so it is better to use Markov Switching Vector Autoregressive Models (MSVAR). MSVAR is a combination of vector autoregressive models and hidden markov models. Daily return of Rupiah buying rate against the USD and Euro are economic variables that are fluctuated and they can explain economic condition of a country. The best model of five order iteration is MS (2) - VAR (4) with the smallest AIC value, that is -1460.48. Maximum Likelihood Estimation is a method to get parameters estimation. With 73 data, the return rates has transition probability 0.08 from crisis to normal state, while the transisition probablity of the opposite condition is 0.6. Expected value being at normal state is 13.10 days and being at crisis state is 1,68 days.